2009
DOI: 10.1093/tropej/fmp001
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effect of Lactobacillus rhamnosus on quantitative reduction of faecal rotavirus shedding in children

Abstract: Beneficial effects of probiotics in acute infectious diarrhoea in children are mainly seen in watery diarrhoea and viral gastroenteritis. Lactobacillus rhamnosus, one the most extensively studied probiotic strains, is effective in shortening courses of acute diarrhoea in children. However, the dose-dependent effect of Lactobacillus upon quantification of faecal rotavirus shedding in humans remains little known. Thus, an open-label randomized trial in 23 children with acute rotaviral gastroenteritis was underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 11 publications
4
46
0
Order By: Relevance
“…L. sporogenes daily administered to newborns during 1 year, prevented the incidence and also diminished the duration of acute RVs diarrhea (37). Fang et al (38) demonstrated that a minimal effective dose of L. rhamnosus significantly reduced fecal shedding RVs concentration in pediatric patients. Although the administration of lyophilized Lactobacillus paracasei strain ST11 daily for 5 days had a clinically significant benefit in the management of non-RVs-induced diarrhea, ST11 treatment against severe RVs diarrhea was ineffective (39).…”
Section: Beneficial Effects Of Immunobiotics In Rotavirus Infectionmentioning
confidence: 99%
“…L. sporogenes daily administered to newborns during 1 year, prevented the incidence and also diminished the duration of acute RVs diarrhea (37). Fang et al (38) demonstrated that a minimal effective dose of L. rhamnosus significantly reduced fecal shedding RVs concentration in pediatric patients. Although the administration of lyophilized Lactobacillus paracasei strain ST11 daily for 5 days had a clinically significant benefit in the management of non-RVs-induced diarrhea, ST11 treatment against severe RVs diarrhea was ineffective (39).…”
Section: Beneficial Effects Of Immunobiotics In Rotavirus Infectionmentioning
confidence: 99%
“…[8][9][10] LGG was effective in decreasing both duration and frequency of rotaviral diarrhea and also antibiotic-associated diarrhea in neonates. [11][12][13] People consuming L. acidophilus (LA) NCFM had reduced fever, cough, and runny nose.…”
Section: Introductionmentioning
confidence: 99%
“…23 children with acute rotavirus infection were randomised to placebo, low-dose or high-dose L rhamnosus. [142] This trial showed no significant reduction in viral shedding in the low dose group but a significant reduction in the high dose group suggesting that a minimum of 6 x 10 8 CFU (colony forming units) for 3 days has to be given to paediatric patients to achieve a good effect. Other studies [143] also suggest a definite but modest benefit in probiotic use in acute infectious diarrhoea, especially in rotavirus-induced diarrhoea.…”
Section: Infectious Diarrhoeamentioning
confidence: 83%